Revision of Sinomesuropetala daohugensis Boudet, Nel & Huang, 2023 (Odonata: Aeshnoptera: Mesuropetalidae) - Qi, Pengliang; Nel, André; Xiao, Chuantao; Zheng, Daran (Zootaxa, 2023)
The mesuropetalid dragonfly Sinomesuropetala daohugensis Boudet, Nel & Huang, 2023, is here revised based on a new well-preserved dragonfly from the Haifanggou Formation of Inner Mongolia, northeastern China. The new specimen allows us to complete the forewing characters of this species, showing the close relationship of Sinomesuropetala Boudet, Nel & Huang, 2023 with Mesuropetala Handlirsch, 1906. The mesuropetalid dragonflies are currently recorded from the Late Jurassic and Lower Cretaceous deposits of east Asia, East Central South Europe, and southern America, indicating the wide distribution and the possible long-distance migration ability of some basal aeshnopteran dragonflies during these epochs.